2000
DOI: 10.2337/diabetes.49.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of endogenous insulin secretion does not require separate assessment of C-peptide kinetics.

Abstract: The implication of -cell failure as an early defect in t y p e 2 diabetes exacerbates the need for accurate but facile assessment of islet cell secretory rate, particularly in large group studies in which individual assessment of C-peptide kinetics is impractical. This study was designed to examine whether it is possible to obtain accurate secretory rates from the extended combined model, which provides insulin and C-peptide kinetics from plasma measurements of the two peptides. Equimolar intraportal infusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…We found that the variations in the parameters of C-peptide kinetics within our animal population were small: for example, V tot changed little and body weight had no influence in spite of the large variation among animals. Another aspect that made us confident about the correctness of our approach was that C-peptide kinetics, estimated in mice, was comparable to that previously reported in humans [20] and dogs [21]: therefore, it can be considered a valid basis for reconstructing prehepatic insulin secretion by deconvolution of C-peptide measurements.…”
Section: Discussionmentioning
confidence: 49%
“…We found that the variations in the parameters of C-peptide kinetics within our animal population were small: for example, V tot changed little and body weight had no influence in spite of the large variation among animals. Another aspect that made us confident about the correctness of our approach was that C-peptide kinetics, estimated in mice, was comparable to that previously reported in humans [20] and dogs [21]: therefore, it can be considered a valid basis for reconstructing prehepatic insulin secretion by deconvolution of C-peptide measurements.…”
Section: Discussionmentioning
confidence: 49%
“…Insulin secretion was calculated from the C-peptide data using the deconvolution analysis based on a two-compartment model of C-peptide kinetics, as previously described [23].…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…These include the Eaton deconvolution method [15,16], the Insulin SECretion method (ISEC) [17±19] and the combined model with one-compartment [23,24] or two-compartments for C-peptide kinetics [25,26] (see Methods). The deconvolution technique has been used in many physiological and pathological conditions [5, 7, 10, 15, 16, 28±30] and has been simplified by using populationbased kinetic parameters of C-peptide instead of individually determined parameters [17].…”
mentioning
confidence: 99%
“…This model has later been modified to encompass two-compartment C-peptide kinetics [25,26]. We have recently assessed the accuracy of the original deconvolution method and the combined model during slow changes in insulin appearance rates, as seen during an oral glucose tolerance test [31].…”
mentioning
confidence: 99%